PENGARUH BERPIKIR KRITIS TERHADAP HASIL BELAJAR MATEMATIKA SMAN 3 PAREPARE - Dilla Pratiwi (Tautologi: Journal of Mathematics Education, 2024)
Some students have difficulty working on mathematics problems systematically. This shows that the level of critical thinking of students is still very lacking. The level of critical thinking can influence mathematics learning outcomes. The research carried out was an Ex Post Facto type of research using a quantitative approach to determine the influence of the level of critical thinking on mathematics learning outcomes for students in class X MIPA 3 UPT SMA Negeri 3 Parepare. The results of descriptive statistical analysis obtained data which showed that the Critical Thinking Level of class The students' learning outcomes are in the "high" category with an average value of 80.96 with an ideal score of 100. The results of the hypothesis test show that the sig (p) value is 0.000. This value is smaller than the significance level a = 0.05 (0.000 < 0.05), meaning that H_0 is rejected and H_1 is accepted. So it can be concluded that there is a positive influence on the level of critical thinking on the mathematics learning outcomes of students in class Negeri 3 Parepare was 52.9%.